TI_GERICHTE 15.2005.136 vom 22. Februar 2006 , Istanza di restituzione del termine per interporre opposizione. Notifica di atto esecutivo. - TI Tribunale d'appello (2006)
Istanza di restituzione del termine per interporre opposizione. Notifica di atto esecutivo.